Effect of Complete COVID-19 Vaccination on Long COVID among the Nepalese Population - Khaniya, Bipindra; Kharel, Sanju; Laudari, Pratikshya; Upadhyay, Hari Prasad; Laudari, Shankar (Journal of National Heart and Lung Society Nepal, 2025)
Background: Long COVID, or post-acute sequelae of SARS-CoV-2 infection (PASC), refers to the prolonged persistence of symptoms beyond the acute phase of COVID-19. Vaccination has been pivotal in mitigating COVID-19-related morbidity and mortality, but its role in reducing long COVID incidence is still being explored, particularly in countries like Nepal. Methods: A narrative literature review was conducted using Nepalese national datasets, tertiary hospital reports, WHO publications, and peer-reviewed international studies. The objective was to assess the impact of complete COVID-19 vaccination (defined as two or more doses) on the occurrence and severity of long COVID in Nepal. Results: Clinical evidence suggests that individuals fully vaccinated before contracting COVID-19 experienced significantly lower incidence and reduced severity of long COVID symptoms, particularly fatigue, breathlessness, and cognitive dysfunction. Data from Nepal’s healthcare facilities indicate improved post-infection outcomes among the vaccinated group. Conclusion: Complete vaccination demonstrates a protective effect against long COVID. These findings advocate for increased vaccine uptake and more robust epidemiological studies in Nepal.